Headteachers' Instructional Leadership at Community Schools - Danai, Rudra Prasad (AMC Journal, 2021)
This article explores instructional leadership of few head teachers of Dhading district. Due to the primitive model of school leadership, students faced obstacles in achieving educational goals. The objectives of this research are to explore the tradition of the head teachers' leadership of school and the role of the head teachers for the transformation of the educational attempts and achievements. This research followed phenomenological research method. Five head teachers leading the schools for more than a decade were interviewed. The data thus collected were interpreted through coding, categorizing and comparing the key themes. The research finds that the leadership role of the head teachers in the past was responsible for lagging behind the target of the educational achievement as recommended by the curriculum. This study concludes that the school leadership must be cross-threaded in instructional process, pedagogy, information, and communication technology (ICT).